If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3 + 6h + -2 + -3 + -4h = 0 Reorder the terms: -3 + -2 + -3 + 6h + -4h = 0 Combine like terms: -3 + -2 = -5 -5 + -3 + 6h + -4h = 0 Combine like terms: -5 + -3 = -8 -8 + 6h + -4h = 0 Combine like terms: 6h + -4h = 2h -8 + 2h = 0 Solving -8 + 2h = 0 Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + 2h = 0 + 8 Combine like terms: -8 + 8 = 0 0 + 2h = 0 + 8 2h = 0 + 8 Combine like terms: 0 + 8 = 8 2h = 8 Divide each side by '2'. h = 4 Simplifying h = 4
| 5x+40=72 | | 12.50*n-50=200 | | C+87=97 | | x-64=26 | | 2n-9-5-2.4n+4= | | -21=96b+30b | | 8/9=x/9 | | 3c+5=29 | | x+82=16 | | x^2-9x-x-24=0 | | -4x^2=3x^2-6x | | (3x-1)(3x-1)-5=0 | | 3(x-6)=6x+3 | | r+(-11)=-4 | | 12x-78=2x+132 | | 3(3-y)+1=33 | | y=2/3*4 | | 8e-7-3=6 | | -(h/4)=3/2 | | y=2/3*-4 | | 6+2+10f-4= | | A(x+6)=2(x-1) | | -15+8x=13+6x | | 4x+x=19-2 | | -24=6+35t | | (7n+5)(4n+5)=0 | | 8x=3-7y | | -5x-6=-6x+17 | | x^2+18x+91=0 | | 1-3(-2)=7 | | (x/8)=(x/9)-15 | | 16/4-3 |